2020
DOI: 10.1590/s1678-4634202046205233
|View full text |Cite
|
Sign up to set email alerts
|

Livros didáticos de educação física: um balanço da produção acadêmica

Abstract: Resumo Objetivou-se, neste artigo, apresentar um balanço da produção acadêmica (artigos, trabalhos de conclusão de curso, dissertações e teses) a respeito dos Livros Didáticos de Educação Física (LDEF) a partir do questionamento acerca do uso de livros ao longo da história dessa disciplina escolar no Brasil. Utilizou-se como referencial teórico-metodológico os trabalhos de Bardin (1977), Choppin (1992, 2004) dentre outros, o que nos permitiu delinear um panorama das produções nacionais acerca dos LDEF, sua dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The academic production involving the theme of textbooks for Physical Education at school has shown that the use of this pedagogical resource, throughout the history of this curricular component in Brazil, is recent, with the first record found dating from 1993 (Loureiro & Moreira, 2020). In this context, Souza Júnior et al (2015) sought to identify, through literature analysis, factors that contributed to the existing gap between Physical Education and textbooks, concluding that the historical legacy of the area has been one of the main drivers of this gap.…”
Section: National Brazilian Textbook Programmentioning
confidence: 99%
“…The academic production involving the theme of textbooks for Physical Education at school has shown that the use of this pedagogical resource, throughout the history of this curricular component in Brazil, is recent, with the first record found dating from 1993 (Loureiro & Moreira, 2020). In this context, Souza Júnior et al (2015) sought to identify, through literature analysis, factors that contributed to the existing gap between Physical Education and textbooks, concluding that the historical legacy of the area has been one of the main drivers of this gap.…”
Section: National Brazilian Textbook Programmentioning
confidence: 99%